A Guide to Living with Wild Cats - Venetia S. Briggs; Rebecca G. Harvey; Frank J. Mazzotti; William M. Giuliano (EDIS)
In Belize, the Lamanai Field Research Center and University of Florida are studying cats using camera traps placed in a variety of locations on private lands. This research suggests that more wild cats live near farms than people are aware of. This 3-page informational brochure highlights 5 species of wildcats living in the area of the study, tips for keeping livestock safe, and local contacts. Written by Venetia S. Briggs, Rebecca G. Harvey, Frank J. Mazzotti, and William M. Giuliano, and published by the UF Department of Wildlife Ecology and Conservation, October 2011. Reviewed October 2014.